Characterization of brittleness index of gas shale and its influence on favorable block exploitation in southwest China - Liu, Guojun; Shang, Delei; Zhao, Yuan; Du, Xidong (Frontiers in Earth Science, 2024)
The microstructure, mineral composition, total organic carbon content, etc., of gas shale are crucial parameters for shale reservoirs, which can directly/indirectly affect shale brittleness, fracturing effect, adsorption ability and production efficiency. The study proposed a workflow to characterize the physical and mechanical parameters of Lower Silurian Longmaxi shale outcrop samples extracted from the favorable block in Changning, Sichuan, southwest China. This study elaborated on the influence of these physical and mechanical characteristics and proposed a corresponding brittleness index on shale extraction. In addition, it put forward corresponding suggestions for development and risk control. For a better understanding the mechanisms of shale gas storage and production, XRD, XRF, SEM, low temperature Nitrogen adsorption method, nuclear magnetic resonance and other measurements were employed to analyze and study the mineral composition, microstructure, and adsorption performance of shale. The results demonstrated that the pores of shale are mainly slit pores; there are diverse pore types in shale, mainly including intergranular pores, mineral particle dissolution pores, and internal pores of organic matter; The samples with relatively low porosity also noticeably exhibit ultra-low permeability, and the nanopore structure is remarkably significant, with distribution primarily in range of 5 ~ 237 nm.Finally, a brittleness index considering the influence of water content and the mechanical properties was proposed, and the coupling interaction of various minerals components and mechanical properties on the brittleness index can more objectively reflect the brittleness characteristics of deep shale formation.